Peningkatan Minat Literasi Melalui Kegiatan Literasi Numerasi dan Literasi Digital - Tsany, Rakan; Rahayu, Devita; Fahmi Amrullah, Reinaldy; Elza Nurhusna, Liviya; Syahyuningsih, Khofifah; Farah Afida, Isma (Journal of Comprehensive Science, 2024)
The Community Service Program with the theme "Literacy Village" is part of an effort to overcome this challenge. Through Kukerta MBKM (Merdeka Belajar Kampus Merdeka), students are expected to be able to contribute directly to the development of literacy culture in villages in need. This activity aims to improve the reading, writing, and critical thinking skills of village communities, especially students. Jake Village, located in Kuantan Tengah District, Kuantan Singingi Regency, in the context of developing the Literacy Village program. With the increasing demands of the digital era, it is important for village communities to master numeracy literacy and digital literacy as a basis for facing challenges and taking advantage of existing opportunities. Jake Village, which is faced with educational challenges, where the literacy level of the population still needs to be improved. Therefore, the numeracy literacy and digital literacy programs are expected to provide access to the community to understand and apply basic technological concepts that are essential in everyday life. The method applied to increase interest in literacy is by providing an understanding of reading, numeracy, and digital literacy. The results achieved are that the school is able to make this literacy program a weekly routine that makes this program sustainable. It can be concluded that literacy interest can be built in various ways, one of which is providing an understanding to the community and students about the importance of reading, numeracy, and digital literacy.